Perbandingan telur cacing soil transmitted helminths pada daun kemangi (Ocimum sanctum) dengan metode flotasi dan sedimentasi - Hidayati, Lisa; Dewi, Sri Rohmanti (Fakultas Kedokteran, Universitas Palangka Raya, 2023)
Basil is a type of vegetable that is found the most as a carrier of STH (Soil Transmitted Helminths) is basil (Ocimum sanctum). This study aims to compare the number and types of STH worm eggs in Ocimum sanctum using 2 types of observation techniques, namely flotation and sedimentation. The research method was observational analytic with a laboratory approach. Samples were taken from vegetable farmers as much as 60 g then divided into 2 treatments each 30 g for the flotation and sedimentation methods. The results of observations on both STH worm eggs were found. Strongyloides sp. worm eggs found in sedimentation techniques and Ascaris sp, Trichuris sp. and hookworms were found in both observation methods. The average value of worm eggs in the flotation method was 9 and the sedimentation method was 6. This research serves as a reference for the community to always maintain the cleanliness of the food they will consume.